Archaea in the Human Microbiome and Potential Effects on Human Infectious Disease - Stefanie Duller; Christine Moissl-Eichinger (Emerging Infectious Diseases, 2024)
Archaea represent a separate domain of life, next to bacteria and eukarya. As components of the human microbiome, archaea have been associated with various diseases, including periodontitis, endodontic infections, small intestinal bacterial overgrowth, and urogenital tract infections. Archaea are generally considered nonpathogenic; the reasons are speculative because of limited knowledge and gene annotation challenges. Nevertheless, archaeal syntrophic principles that shape global microbial networks aid both archaea and potentially pathogenic bacteria. Evaluating archaea interactions remains challenging, requiring clinical studies on inflammatory potential and the effects of archaeal metabolism. Establishing a culture collection is crucial for investigating archaea functions within the human microbiome, which could improve health outcomes in infectious diseases. We summarize potential reasons for archaeal nonpathogenicity, assess the association with infectious diseases in humans, and discuss the necessary experimental steps to enable mechanistic studies involving archaea.